การเสริมกำลังอาคารเรียนคอนกรีตเสริมเหล็กด้วยองค์อาคารยึดรั้งไร้การโก่งเดาะ - Panyakapo, Phaiboon; Ponpimonpat, Puripong (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 2 (2014): May-August 2014, 2014)
งานวิจัยนี้เป็นการเสริมกาลังโครงสร้างอาคารเรียนคอนกรีตเสริมเหล็กเพื่อต้านทานแรงแผ่นดินไหวด้วยองค์อาคารยึดรั้งไร้การโก่งเดาะ ในการศึกษานี้เลือกอาคารคอนกรีตเสริมเหล็กสูง 3 ชั้นซึ่งเป็นอาคารเรียนในสังกัดกระทรวงศึกษาธิการเพื่อใช้เป็นอาคารต้นแบบ ในการประเมินกาลังโครงสร้างอาคาร ได้ทาการจาลองพฤติกรรมการรับแรงอินอิลาสติกของโครงสร้างแบบหน้าตัดไฟเบอร์ โดยใช้โปรแกรม PERFORM-3D และวิเคราะห์โดยวิธีการผลักแบบสถิตไม่เชิงเส้นแบบ 3 มิติ และด้วยวิธีพลศาสตร์ไม่เชิงเส้น โดยใช้คลื่นแผ่นดินไหวบริเวณพื้นที่จังหวัดแพร่ เพื่อประเมินระดับความเสียหายและรูปแบบความเสียหายของโครงสร้าง ผลการวิเคราะห์พบว่า สาหรับโครงสร้างอาคารเดิม ผนังก่ออิฐโดยรอบอาคารและเสาคอนกรีตบริเวณขอบอาคาร เกิดการแตกร้าว โดยค่าความเครียดของคอนกรีตและเหล็กเสริมที่เสาบริเวณปลายบนและล่างที่จุดต่อเสาและคาน มีค่าสูงเกินกว่าข้อกาหนด หลังการเสริมกาลังโครงสร้างอาคารด้วยวิธีองค์อาคารยึดรั้งไร้การโก่งเดาะบริเวณขอบอาคาร ผลการศึกษาไม่พบความเสียหายของเสาอาคาร และค่าการเคลื่อนที่สัมพัทธ์ระหว่างชั้นอาคารมีค่าไม่เกินข้อกาหนดตามมาตรฐานการออกแบบ คำสำคัญ: องค์อาคารยึดรั้งไร้การโก่งเดาะ เสริมกาลังโครงสร้าง วิธีการผลักแบบสถิตไม่เชิงเส้นแบบ 3 มิติ วิธีพลศาสตร์ไม่เชิงเส้น ต้านทานแผ่นดินไหว         This research presents the strengthening of reinforced concrete school building with buckling restrained brace. In this study, 3-storey reinforced concrete school building, which is a standard type of the Ministry of Education, was selected as the prototype building. In the seismic evaluation, the structure was modeled as fiber section to represent the inelastic behavior by using PERFORM-3D. Nonlinear static analysis and nonlinear dynamic analysis were performed for Phrae provinces, to investigate the seismic damage of the structure. For the existing building, it was found that, the infill wall and concrete column were cracked around the edge of building. The strains of the concrete and reinforcing steel of column at the beam-column joint were higher than their strain capacities. After the strengthening of reinforced concrete school building with buckling restrained brace around the edge of building, there was no damage at the column, and the inter-story drifts were within the allowable limit according to the design standard. Keywords: buckling restrained brace, strengthening of structure, nonlinear dynamic analysis, nonlinear static analysis.
Keywords: องค์อาคารยึดรั้งไร้การโก่งเดาะ เสริมกาลังโครงสร้าง วิธีการผลักแบบสถิตไม่เชิงเส้นแบบ 3 มิติ วิธีพลศาสตร์ไม่เชิงเส้น ต้านทานแผ่นดินไหว buckling restrained brace, strengthening of structure, nonlinear dynamic analysis, nonlinear static analysis.